In-vitro assessment of antioxidant and cytotoxic activity of ethyl acetate extract of Commiphora mukul - Siva S; L Kalaiselvi; N Pazhanivel; R Gokul (The Indian Veterinary Journal, 2026)
Commiphora mukul (Guggul), native to India, Pakistan, and Bangladesh, is widely used in traditional medicine for cancer, atherosclerosis, rheumatism, and obesity. This study evaluated the phytochemical composition, antioxidant activity and cytotoxic potential of its ethyl acetate extract. Phytochemical analysis confirmed alkaloids, flavonoids, phenols, tannins, steroids, and terpenoids while saponins, glycosides, cyanin, and proteins were absent. The extract showed high flavonoid content (84.54 mg CE/g) and lower phenolic content (9.76 mg GAE/g). DPPH and reducing power assays confirmed strong antioxidant activity. Cytotoxicity evaluated by MTT assay showed 89.24% inhibition at 1 mg/ml, with an IC50 of 46.67 µg/ml, indicating significant therapeutic potential.